PROMOTION OF PRODUCTS SALES AS A WAY TO OVERCOME THE COMMUNICATION GAP IN THE RELATIONSHIP BETWEEN RETAILERS AND CONSUMERS - SIRENKO, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article defines that a system of sales promotion, aimed at revitalization customer’s behavior at the points of sale, is an important assignment of managing their marketing activities. The practical experience of Ukrainian retailers has been explored and the list of sales promotion measures that were effective in Ukrainian retailing is determined. The importance of compliance with existing legislation and business ethics in the formation of sales promotion program is justified. A comparative analysis of the implementation of the marketing event "Black Friday" by its attributes in the United States and Ukraine has been conducted. It is determined that in Ukraine unscrupulous marketing practice of local stores and Ukrainian brands is taking place by misleading the most rational consumers. Recommendations for domestic retailers on the formation of goals of promotion of products sales and maintaining or increase consumer loyalty to local domestic brands have been developed. The urgency of overcoming the communication gap in the relationship between producers (sellers) on the one hand, and consumers – on the other is justified, because the communication gap sometimes reaches such a pitch that the reaction of buyers is getting negative not only in relation to a particular local domestic brand, but also to all similar actions of all the retailers.